Motif, Konstruksi, dan Keadilan Semu dalam Praktik Poligami Kiai Pesantren di Madura - Shofiyullah Muzzammil; Mohammad Affan; Muhammad Alwi HS; Masturiyah Masturiyah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
The phenomenon of polygamy by the kiai of the Pesantren in Madura is rooted in the religious teachings that are intertwined with the legitimacy of the patriarchal socio-cultural structure. The research aims to reveal the motives, construction, and apparent justice in polygamy practices still widely practiced by people in Madura, especially by kiai as central figures in Pesantren. This research includes field research by conducting interviews and observations in two Pesantrens in Madura led by kiai, who practice polygamy. By using the descriptive-analytical method, this article discovers some of the kiai's polygamy motives, among others, as an outlet for the tradition of matchmaking in his family environment, the desire to have many children, especially sons, and to minimize the concentration of conflict between the first and second wives by presenting a next wife. The practice of polygamy by kiai is framed in religious discourse and the socio-cultural structure of the Madurese community through the pesantren habitus, which forms the construction of polygamy as something ordinary, even noble. The polygamy discourse is formed through the standardization of gender roles through the rules of the pesantren and the teaching of the kitab kuning. In preventing the fulfillment of the requirements of justice in polygamy, kiai make a pre-marriage contract with the prospective wife to avoid justice demand. In this construction, women are always conditioned to be accepting and obedient. Thus, religious discourse co-opted injustice with the promise of heaven for every polygamous woman so that the kiai's polygamous family household could survive but in an atmosphere of false justice.